Marriages of More Than Four and its Impacts on Community Perspective of Islamic Law and Indonesian Law: تعدد الزوجات أكثر من أربع النسوة وأثارها في المجتمع عند منظور الشريعة والقانون الإندونيسي - Yahya Muhammad Thaib; Rania Mahmoud ELSakhawy; Muthoifin; Thufail Al-Mutawakkil (Walidem Institute and Publishing (WIP), 2023)
The objectives of the research are to find out the ruling on the marriage of more than four women under the bondage of a man according to Islamic jurisprudence and law in Indonesia, and to know the sayings of scholars about the multiple women of more than four and to know the dispute between them and the most correct of their sayings. The way of thinking in this research is qualitative research, where the researcher focuses on studying the process using inductive and comparative inferential. In this research, the type of research used a desk approach. Marriage of more than four women is forbidden according to the texts of the Qur’an and Sunnah. And it is proven that the Messenger of God, upon him be peace, commanded those who work together with more than four women by separating from some of their wives so that the number of their wives is four. He did not lay down the statutory laws about marrying more than four women but was mentioned in the fatwas of Indonesian scholars. The fatwa from the Council of Scholars Indonesia and the group of proposals in Indonesian Islamic rulings saw the prohibition of marriage with more than four women. It was reported by some scholars that they permitted it, and it is the most likely view. He who marries more than four women according to Islamic jurisprudence, knowing the prohibition, has committed adultery and has the punishment for stoning, and the fifth child is attached to his mother, not to his father.